Education in Vaccinology: An Important Tool for Strengthening Global Health - Lambert, Paul-Henri; Podda, Audino (Frontiers in Immunology, 2018)
Over the past 20 years, education of scientists and public health professionals in Vaccinology has increased dramatically. There are now many international, regional, and national courses that provide education in vaccinology. The proliferation of these courses and the high number of applications submitted demonstrate the increasing and continuous need for improved education in this field since, generally, comprehensive vaccinology training is not offered to medical and/or biological sciences students as part of their Universities courses and consequently there is insufficient knowledge of vaccine topics among health-care providers. Multidisciplinary vaccinology courses have not only educational purposes but they may also contribute to strengthening the development, testing, and use of vaccines, which remain the most efficient tool for infectious disease prevention. The courses available have a varied focus and prioritize topics based on the trainees’ different levels of professional exposure and requirements. Overall, they might be classified in two key categories: (i) courses targeting students who, after their university studies in Medicine, Biology, etc., develop a strong interest in vaccines, would like to learn more about the various aspects of vaccinology, and potentially develop a career in this field (postgraduate courses); (ii) courses targeting postdoctoral professionals, who already have a sufficiently broad knowledge of vaccinology, but would like to develop stronger skills to be able to play a leading role in decision-making for vaccine development (advanced professional courses). Both postgraduate and professional courses are available and are based on comprehensive curricula. In the future, particular attention should be paid to include in the training curricula topics that might help vaccine development, efficient and sustainable vaccine introduction through epidemiologically sound vaccination programs, and best practices to address associated challenges, including vaccine hesitancy which could become a threat to successful implementation of vaccination programs, particularly in developed countries. In addition, it appears that the next phase of vaccinology training could benefit from a global and more structured platform that could facilitate exchanges and collaboration and amplify the current capacity for disseminating vaccine education for future vaccinology leaders around the world. This would be favored by synergizing the efforts currently devoted to vaccinology education. To initiate this process of analysis and systematization, a multinational effort is needed.